Valer, Camacho y los “cautivos de la Inquisición”: Sevilla 1540-1541 - Boeglin, Michel (Cuadernos de Historia Moderna, 2007)
Much has been written about Rodrigo de Valer, presenting him as one of the first reformers in Andalucia, although how he came to discover Lutherian doctrine, or even if he knew of it, is often overlooked. New documents invite a reappraisal of the chronology of his inquisitorial trials and suggest that Valer not only had leanings towards evangelism but also, contrarily to what his protestant biographers wrote, to more popular movements oriented to superstition and miraculous apparitions and so forth. This was at a time when the aim of an ecclesiastic reform was strongly shared by the population as well as the aim of a Council that would permit in the 1540 to debate of Luther doctrines within the Church.